The Zero Suicide Model: Applying Evidence-Based Suicide Prevention Practices to Clinical Care - Brodsky, Beth S.; Spruch-Feiner, Aliza; Stanley, Barbara (Frontiers in Psychiatry, 2018)
Suicide is reaching epidemic proportions, with over 44,000 deaths by suicide in the United States, and 800,000 worldwide in 2015. This, despite research and development of evidence- based interventions that target suicidal behavior directly. Suicide prevention efforts need a comprehensive approach, and research must lead to effective implementation across public and mental health systems. A 10-year systematic review of evidence- based findings in suicide prevention summarized the areas necessary for translating research into practice. These include risk assessment, means restriction, evidence- based treatments, population screening combined with chain of care, monitoring and follow-up. In this article, we review how suicide prevention research informs implementation in clinical settings where those most at risk present for care. Evidence-based and best practices address the fluctuating nature of suicide risk, which requires ongoing risk assessment, direct intervention and monitoring. In the U.S., the National Action Alliance for Suicide Prevention has put forth the Zero Suicide (ZS) Model, a framework to coordinate a multi-level approach to implementing evidence-based practices. We present the Assess, Intervene and Monitor model for Suicide Prevention (AIM-SP) as a guide for implementation of ZS evidence-based and best practices in clinical settings. Ten basic steps for clinical management model will be described and illustrated through case vignette. These steps are designed to be easily incorporated into standard clinical practice to enhance suicide risk assessment, brief interventions to increase safety and teach coping strategies, and to improve ongoing contact and monitoring of high-risk individuals during transitions in care and high risk periods.